Key Success Factors in Entrepreneurial Development among Women Micro-Entrepreneurs in Malaysia - Tirumalaisamy, Vikneswary; Vasudevan, Asokan; Balakrishnan, Rajani; Mohammad, Suleiman Ibrahim Shelash; Vasumathi, A.; Al-Adwan, Ahmad Samed; Al Kurdi, Barween (International Review of Management and Marketing, 2024)
This study explores factors influencing entrepreneurial development among women microentrepreneurs in Malaysia. Using self-administered questionnaires distributed to 50 participants, the research examined four key factors: family support, business prospects, sociocultural factors, and government support, with entrepreneurial development as the dependent variable and perception of success as a mediator. The data was analyzed using SmartPLS software. Results indicated that most variables had reliable Cronbach Alpha values, though issues with discriminant validity were found. The structural model showed substantial explanatory power, and most path coefficients indicated positive relationships, except for the link between government support and entrepreneurial development. However, only one hypothesis was accepted, revealing that socio-cultural factors significantly influence entrepreneurial development through the perception of success. The study suggests that future research should focus on specific sectors within microenterprises and include a larger sample size for a broader understanding of women’s economic contributions. This research provides valuable insights for policymakers aiming to enhance support for women microentrepreneurs in Malaysia.